2013
DOI: 10.1007/s00417-013-2339-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term anatomical and functional outcomes of idiopathic macular hole surgery. The yield of spectral-domain OCT combined with microperimetry

Abstract: Postoperative outer retinal layer integrity is associated with better final retinal sensitivity. Further studies are warranted to assess the role of SD-OCT and microperimetry in the pre- and postoperative evaluation of idiopathic macular holes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
2
20
0
1
Order By: Relevance
“…However, anatomical closure of a hole does not always correlate with a good functional result (6,17,18) . Although various preoperative SD-OCT parameters have been examined to estimate postoperative visual prognosis, studies have reported the lack of any consistent volumetric or structural feature that is closely correlated with anatomical and functional surgical successes (15)(16)(17)(18) . In this study, there was no statistical difference in MHV measurements between eyes with and without disease recurrence; however, lower preoperative BCVA scores were found in eyes with relapsing MH.…”
Section: Discussionmentioning
confidence: 99%
“…However, anatomical closure of a hole does not always correlate with a good functional result (6,17,18) . Although various preoperative SD-OCT parameters have been examined to estimate postoperative visual prognosis, studies have reported the lack of any consistent volumetric or structural feature that is closely correlated with anatomical and functional surgical successes (15)(16)(17)(18) . In this study, there was no statistical difference in MHV measurements between eyes with and without disease recurrence; however, lower preoperative BCVA scores were found in eyes with relapsing MH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a significant correlation between the presence of such abnormalities and postoperative visual prognosis has been recently reported (16)(17)(18)(19)(20) . In this study, MHV was not found to be associated with the postoperative re-establishment of any of the studied parameters of external retinal microstructure.…”
Section: Discussionmentioning
confidence: 96%
“…The data were stored in a computerized database and analyzed using Statistical Package for Scientific Studies for Windows v. 16.0 (SPSS Inc., Chicago, IL, USA). Normal distribution analysis of the data was performed using the Kolmogorov-Smirnov test; moreover, the chi-square test, the paired t-test, Student's t-test, and the MannWhitney U test were performed for statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,7 Several authors have investigated the relationship between functional disturbances and SD OCT findings in various retinal diseases including ERM. [8][9][10] It appears that integrity of external retinal layers and foveal thickness are closely correlated with visual parameters. [11][12][13] Since the first 6 cases of successful ERM removal were reported by Machemer in 1978, the surgical procedure has steadily improved.…”
mentioning
confidence: 99%